The Use of English as a Lingua Franca in Business Communication: A Case Study of Applied Foreign Language Students - Valensya Annisa Ikhsan; Lilis Lamsehat Panjaitan (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
English as lingua franca, the main focus is on achieving mutual understanding rather than using perfect grammar or sounding like a native speaker. However, students often face challenges in speaking fluently due to different accents, proficiency levels, and cultural references, which can lead to misunderstandings and communication disruption. Such strategies help speakers maintain politeness, ensure clarity, and improve efficiency in their interactions. In professional contexts, these three strategies are important to support smooth and successful communication between individuals from different linguistic and cultural backgrounds. This study aimed to fill the gap by focusing on the real experiences during internship of Applied Foreign Language students involved in business communication using English as a lingua franca. Using a qualitative descriptive approach, the research found that students employed various communication strategies to manage language gaps. The use of politeness, clarity, and efficiency strategies helped to improving their confidence, enhancing their professional self-respect, and encouraging more active participation in workplace interactions. In conclusion, these communication strategies are effective tools that help students handle language challenges, maintain clear and respectful communication, and engage more fully in professional settings where English functions as a Lingua Franca.